Effect of Boundary Layer and Rotor Speed on Broadband Noise from Wind Turbines - Vasishta Bhargava; Rahul Samala (Journal of Aerospace Technology and Management, 2019)
Trailing edge surface of aerofoil is an important source of broadband aerodynamic noise production. In this paper, three aerofoil self-noise mechanisms from turbulent boundary layer near trailing edge surface are studied. Numerical computations were performed for a three bladed 2 MW horizontal axis upwind turbine of blade length 37 m and source height of 80 m, for wind speeds of 8-15 m/s. A weighted 1/3rd octave band sound power levels (SPL) are evaluated for receiver located at distance of total turbine height and at 2 m above ground. The results obtained for sound power level using baseline models showed maximum values occurring between 300 Hz and 1 kHz region of spectrum. The trends for BPM model showed a reduction of ~2 dBA near 1 kHz region of spectrum at 10 m/s, but Grosveld’s and Lowson model were identical and agreed over the entire spectrum. The effect of rotational speed on sound power levels using three baseline models are illustrated at a wind speed of 8 m/s for 2 MW turbine. Results showed that for a change of ±10% rotor speed from the rated value, there is an increase of 2 to 6 dBA over the entire sound spectrum due to differences in blade tip speed.